NILAI SIKAP DAN KARAKTER DALAM PERIBAHASA INGGRIS SEHUBUNGAN DENGAN SAPI - N.K. Mirahayuni; Susie Chrismalia Garnida (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
This paper discusses social wisdom, values and attitudes expressed in English proverbs relatedto cow. This paper is a part of an ongoing study on values in English and Indonesian proverbs relatedwith horse, cow, bufallo and donkey. Proverbs are generally identified from its brief and memorablewords or sentences that express truth and reality and in many ocassions express advice reflected fromdaily experiences and general observation that are expressed in a fixed and effective language forms thatthey are memorable and are ready to use as an effective rhetorical device in both oral and writtenlanguage (Mieder, 2004). Proverbs express an awareness of human condition and weakness that voices ofadvice that are expressed in this special language may be sounded with clarity, humour, wit and insights(Barajaz, 2010). The paper reports the descriptive qualitative study on ninety (90) English proverbsrelated to cow. The data of the study are collected from various printed and electronic sources of Englishproverbs. The study found that a number of good wisdom, values and attitudes are taught and transmittedusing cow as the keyword such as the value of acquired over inherited social status, discipline andresponsibility, hardworking, minimizing trouble, habit formation and others. The study may be useful inthe context of English language learning, that English learners may learn the socio-cultural valueswrapped in the daily language expressions such as proverbs.Keywords: English proverbs, socio-cultural values